2002
DOI: 10.1038/sj.ejcn.1601319
|View full text |Cite
|
Sign up to set email alerts
|

Study of the effect of a liquid nutrition supplement on the nutritional status of psycho-geriatric nursing home patients

Abstract: Objectives: To evaluate the acceptance of a multinutrient liquid nutrition supplement in psycho-geriatric nursing home patients and the effect on weight, plasma nutrients and activities of daily life. Design: Double-blind, placebo-controlled 12-week intervention study. Setting: Two nursing homes in Boxtel, The Netherlands. Subjects: Forty-two (body mass index (BMI) < 23 kg=m 2 for men or < 25 kg=m 2 for women) psycho-geriatric nursing home patients aged 60 y or over. Interventions: Provision with a complete mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
62
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(69 citation statements)
references
References 25 publications
(32 reference statements)
5
62
0
1
Order By: Relevance
“…On the basis of an MMSE score of 23.5 points (p 10 -p 90 : 10.7-27.3) and Barthel Index of 16, we may characterize our population of 80 years of age on an average as an institutionalised, borderline-demented population, but reasonably independent for activities of daily living. Baseline mean energy, protein, fat intake and intakes of vitamins and minerals of our population were much lower than that of the independently living Dutch elderly of the SENECA study Moreiras et al, 1991), but were similar to the low intakes observed in Dutch nursing-home residents (van-der-Wielen et al, 1995;Wouters-Wesseling et al, 2002). One-third of our participants had an energy intake below 6.3 MJ/day, which is one of the indicators of risk for inadequate micronutrient intakes (de-Groot et al, 1996).…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…On the basis of an MMSE score of 23.5 points (p 10 -p 90 : 10.7-27.3) and Barthel Index of 16, we may characterize our population of 80 years of age on an average as an institutionalised, borderline-demented population, but reasonably independent for activities of daily living. Baseline mean energy, protein, fat intake and intakes of vitamins and minerals of our population were much lower than that of the independently living Dutch elderly of the SENECA study Moreiras et al, 1991), but were similar to the low intakes observed in Dutch nursing-home residents (van-der-Wielen et al, 1995;Wouters-Wesseling et al, 2002). One-third of our participants had an energy intake below 6.3 MJ/day, which is one of the indicators of risk for inadequate micronutrient intakes (de-Groot et al, 1996).…”
Section: Discussionsupporting
confidence: 73%
“…Two-thirds of the participants were allocated to the intervention (n ¼ 119) group and one-third to the placebo drink (n ¼ 57) group. We based this unequal distribution of participants on the positive results on nutritional status in a pilot study (Wouters-Wesseling et al, 2002).…”
Section: Study Populationmentioning
confidence: 99%
See 2 more Smart Citations
“…Up to 70% of older adults (≥65 years) living in long-term care (LTC) homes are at risk for undernutrition (Wouters-Wesseling et al 2002;Isenring et al 2012), which can lead to mortality and morbidity (Pirlich and Lochs 2001). Micronutrient malnutrition exists and is poorly studied in LTC older adults (Lam et al 2015a(Lam et al , 2015b.…”
Section: Introductionmentioning
confidence: 99%